SAT0336 Measurement properties of the minimal disease activity criteria for psoriatic arthritis. (12th June 2018) - Coates, L.C.; Strand, V.; Wilson, H.; Stolshek, B.S.; Samad, A.; Chung, J.; Gladman, D.D.; Mease, P.
Abstract : Background: Psoriatic arthritis (PsA) is a heterogeneous inflammatory joint disease, which generally occurs in combination with psoriasis. Key defining features include joint inflammation, psoriasis, nail changes, axial disease, dactylitis, and enthesitis. A composite endpoint that captures all aspects of the disease is critical to understanding disease activity. Recognising the need for a measure of acceptable disease status that equates to a clinically meaningful outcome for patients, the Group for Research and Assessment of Psoriasis and PsA followed methodology from Outcome Measures in Rheumatology to develop the Minimal Disease Activity (MDA) criteria. 1 Since initial publication of the MDA criteria, which consist of physician and patient–reported measures, they have been used in a number of randomised controlled trials (RCTs) and long-term observational studies (LOS). These studies provide an opportunity to systematically evaluate the measurement properties of the MDA. Objectives: To examine evidence of the validity and the ability of the MDA to detect change in published PsA studies. Methods: A targeted literature review was conducted in MEDLINE and EMBASE to identify publications that provided evidence of the validity or ability of the MDA criteria to detect change. LOS that reported data without a comparator and studies that examined the relationship between achievement of MDA and baseline variables were excluded. Abstracts of conference proceedings were included if they reported on phase 3 results not yet formally published. Relevant data were extracted and summarised in tabular format, and reviewed by an independent investigator. Results: 20 publications were identified that met inclusion criteria. In both LOS and RCTs, patients in MDA consistently had decreased inflammatory markers (ie CRP), decreased radiographic joint erosions and progression of structural damage over time, and reported less disease impact on patient-reported outcomes. The consistency of these findings in both LOS and RCTs provide support for the validity of the MDA. Nine RCTs demonstrated superior efficacy to the respective comparator arm. All nine of these RCTs also reported a significantly greater percentage of patients in the active treatment arms met MDA criteria vs. Placebo. These results provide support for the ability of the MDA to detect between-subjects change. Two LOS were also identified that reported on the association with achievement in MDA following initiation of treatment with bDMARDs. demonstrated a significant likelihood of patients beginning treatment with bDMARDs to meet MDA after 4, 6, and 12 months of treatment, providing support for the MDA to detect change in a real-world setting. Conclusions: Published evidence indicates that the MDA is a validated measure with the ability to detect change in PsA patients. The MDA criteria offer a practical, holistic, and clinically meaningful endpoint for patients and clinicians to assess the impact of specific treatment interventions on PsA disease activity. Reference: [1] Coates LC, Helliwell PS. Arthritis Care Res (Hoboken)2010;62(7):965–969. Disclosure of Interest: L. Coates Grant/research support from: AbbVie, Pfizer, Novartis, Celgene, Consultant for: AbbVie, Amgen, BMS, Celgene, Galapagos, Janssen, Eli Lilly and Co., MSD, Novartis, Pfizer, Prothena, Sun Pharma, UCB, V. Strand Consultant for: AbbVie, Amgen, Bayer, Boehringer Ingelheim, Celltrion, Crescendo, Genentech/Roche, GSK, Janssen, Lilly, Merck, Novartis, Pfizer, Samsung, Sandoz, UCB, H. Wilson Consultant for: Amgen Inc., B. Stolshek Shareholder of: Amgen Inc., Employee of: Amgen Inc., A. Samad Shareholder of: Amgen Inc., Employee of: Amgen Inc., J. Chung Shareholder of: Amgen Inc., Employee of: Amgen Inc., D. Gladman Grant/research support from: Amgen, AbbVie, Celgene, Eli Lilly, Janssen, Novartis, Pfizer, UCB, Consultant for: AbbVie, Amgen, BMS, Celgene, Eli Lilly, Janssen, Novartis, Pfizer, UCB, P. Mease Grant/research support from: AbbVie, Amgen, Bristol Myers Squibb, Celgene, Janssen, Lilly, Novartis, Pfizer, Sun, UCB, Consultant for: AbbVie, Amgen, Bristol Myers Squibb, Celgene, Janssen, Lilly, Novartis, Pfizer, Sun, UCB, Speakers bureau: AbbVie, Amgen, Bristol Myers Squibb, Celgene, Genentech, Janssen, Novartis, Pfizer, UCB